The Curriculum Management Models of Laboratory Schools in Lptk - Bahri, Samsul; Bestari, Prayoga; Sinaga, Obsatar (Journal of Ecohumanism, 2024)
This study examines the curriculum management models in laboratory schools under the Educational Personnel Training Institutions (LPTK) at four universities: Universitas Pendidikan Indonesia (UPI), Universitas Negeri Jakarta (UNJ), Universitas Negeri Padang (UNP), and Universitas Pendidikan Ganesha (Undiksha). Laboratory schools play a vital role as practical training grounds for prospective teachers and as centers for educational innovation development. This research employs a qualitative method with a descriptive approach to explore the various curriculum management models implemented in these laboratory schools.The findings indicate that the curriculum management in each laboratory school has its unique characteristics based on the vision and mission of each university. However, there is a general focus on developing curricula that align with national education needs and local content. Effective evaluation and supervision are key to successful curriculum implementation in laboratory schools. Furthermore, laboratory schools also play a strategic role as centers for innovative education and serve as models for other schools in preparing professional teacher candidates.